Analysis of the Regulation of Key Risk Factors to Road Traffic Accident in Ethiopia and Challenges for Enforcement - Eshetu, Bereket (Bahir Dar University Journal of Law, 2023)
Road Traffic Death is a common tragedy in many parts of the world, yet one that rarely receives the attention it merits. More than one million three hundred thousand fifty people globally, and three thousand five hundred people in Ethiopia are being killed in road accidents every year. Regrettably, working-age groups make up a large proportion of those killed and injured. Accordingly, this article examined how far comprehensive is the Ethiopian law in addressing key risk factors for traffic accident. Particularly, it examined the comprehensive regulation of key risk factors to road traffic deaths and injuries namely: speeding, drink–driving, use of seatbelts, child restraints, and motorcycle helmets, in light of the globally accepted practices. The result showed, despite the effort made to incorporate several rules, there are still substantial loopholes in meting out the appropriate penalties. Further, the non-application of point demerit penalty system stipulated under the law, limited resource, understaffing and lack of patrolling vehicles/motorcycles, Traffic Controllers’ lack of commitment for enforcing traffic laws, lack of publicity and poor road engineering works are, among others, identified as the major obstacles to effective enforcement of traffic regulation.